KORELASI FAKTOR AIR SEMEN TERHADAP KUAT TEKAN PERVIOUS CONCRETE - Nabila Sakinah; Gusneli Yanti; Shanti Wahyuni Megasari (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2022)
Pervious concrete is concrete that uses little or no fine aggregate, coarse aggregate, water, and cement. The compressive strength of previous concrete is greatly influenced by the composition of the mixture and the effort of compaction. One of the factors that influence the manufacture of pervious concrete is the water-cement ratio (wcr). The research objective was to determine the correlation between the water-cement ratio and the compressive strength of paving block pervious concrete, using variations in the cement water factor of 0.30; 0.35, and 0.40. The method used is by ACI-522R-10, the size of the uniform coarse aggregate is 9.5 - 19 mm and the ratio of cement to coarse aggregate is 1: 4. The additive used is the Master Glenium ACE 8595 concrete additive with the addition of 0% and 1.0%. The test object used was in the form of a cube with a size of 15 cm on each side and the number of specimens for each variation of the fas value was 3 specimens. The results obtained in the test obtained the strength value of pervious concrete in the IV mixture with an average value of 2.87 MPa, with a water-cement ratio value of 0.30 with the addition of 1.0% additive. namely y = -165.33x2 + 124x – 20.677 with the correlation equation of r2 = 0.8794.